Children working it out together: A comparison of younger and older learners collaborating in task based interaction - Oliver, Rhonda; Philp, J.; Duchesne, S. (2017)
© 2017 This paper describes peer interaction among children with English as an Additional Language (EAL) in primary schools. Through linguistic analysis it provides an exploratory examination of the nature of their collaborations, how they work together and the ways they interact as they complete classroom task pair work. 42 children from two junior and two senior classes of intermediate level English from four EAL reception classrooms participated. Data comprised recordings and transcriptions of the interactions of 11 pairs of younger (5–8 years) and 10 pairs of older (9–12 years) children as they completed five tasks over two weeks. An analysis of the language used demonstrated variation in: (a) the way the children worked socially, enjoyment during task work, cooperating and achieving reciprocity, and how they resolved conflict when it occurred; (b) their task management and on- and off-task talk; (c) the language they used for learning, demonstrating their cognitive involvement, and; (d) their attention to content and linguistic aspects of the task. Differences were also observed to occur according to the age of the learners. Together the results from this study suggest the need to consider task based interaction beyond simply the linguistic and operational levels alone.